Cangar Bridge as a Liminal Space: An Analysis of Mythical Speech Acts, Liminality, and Mystical Constructions in Digital Narratives - Primadani, Kiki Malika; Suhardi (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Cangar Bridge is not merely a physical infrastructure connecting Batu City and Mojokerto Regency in East Java, but has evolved into a liminal space laden with mythological, spiritual, and cultural meaning. This study analyzes the mythological speech acts (tindak tutur mitos) that circulate in the local community around Cangar Bridge, examining how these utterances function as directive and declarative acts that reinforce the bridge’s spatial identity as a threshold between the world of the living and the realm of spirits. Drawing on Victor Turner’s liminality theory, J.L. Austin and J.R. Searle’s speech act theory, and Roland Barthes’s mythological analysis, this qualitative study reveals how the historical trauma of colonial-era construction involving coercive labor and fatalities has sedimented into local oral traditions that frame the bridge as an "angker" (haunted/forbidding) site. These mythological speech acts are not mere folklore; they perform social functions of spatial regulation, identity construction, and collective memory preservation. In the digital era, these myths have been reactivated and amplified through viral content on social media, creating a recursive loop between archaic oral tradition and contemporary digital folklore, with direct implications for the phenomenon of aesthetic death popularized as "Mawar Hitam."